THE CONTRIBUTIONS OF MNCs TO ECONOMIC AND SOCIAL CHANGES OF NEPALESE SOCIETY - Siti Nurhasanah (HI 15 UMY 455, 2015)
*455 This undergraduate thesis discusses about the contributions of the multinational corporations to the economic and social condition of Nepalese Society. Multinational corporations are spreading into the world especially the third-world countries due to several reasons. The third-world countries also receive the existence of MNCs to their countries to increase the economic and social development. Nowadays, MNCs cannot be underestimated again since MNCs have their important role as a non-state actor. Through a qualitative method, this undergraduate thesis emphasizes on the impacts resulted from MNCs existence in Nepal. The theoretical framework of this undergraduate thesis uses the modernization theory which cover the development of the people either the economic or social. The result of the research shows that the Nepalese society has changed from traditional into more modern one. However, it does not mean that the people are more welfare. The economic development of the people is stagnant since the increase of GDP does not directly influence the living standard of the people